The Ludic Drive as Innovation Driver: Introduction to the Gamification of Innovation - Steffen Roth; Dirk Schneckenberg; Chia-Wen Tsai (Creativity and Innovation Management, 2015)
Gamification has recently been receiving increased attention in corporate innovation and business research alike. In this article, we first outline the main streams of research on gamification in the creativity and innovation literature. We then introduce the selection of contributions to this special section by theoretically embedding them in their application contexts. Thus referring to research fields as different as business model innovation, design thinking and crowdsourcing, we indicate theoretical challenges for future research on gamification, among the most important of which we count theoretical approaches to the question of whether and how organizations actually can play with persons.
Keywords: O31; O32; 330; Innovation; Gamification; Crowdsourcing; Business Models; Lego Serious Play; Innovation